Improved artificial bee colony algorithm for large scale colored bottleneck traveling salesman problem - Wenyong DONG; Xueshi DONG; Yufeng WANG (Tongxin xuebao)
In the fields such as intelligent transport and multiple tasks cooperation, the model scale constructed by colored bottleneck traveling salesman problem (CBTSP) tends to large scale, and therefore it is necessary to study the large scale CBTSP and its algorithms. An improved artificial bee colony algorithm (IABC) was applied to solve the large scale CBTSP. IABC employed generating neighboring solution (GNS) to improve artificial bee colony algorithm for CBTSP. GNS generated new solution by deletion and reinsertion operations, during this process, and it can optimized the existed solution for this problem. Experiments show that IABC can demonstrate better solution quality than other compared algorithms for large scale CBTSP.